Precise allele-specific genome editing by spatiotemporal control of CRISPR-Cas9 via pronuclear transplantation - Li, Yanhe (Nat Commun, 2020)
Gene-targeted animal models that are generated by injecting Cas9 and sgRNAs into zygotes are often accompanied by undesired double-strand break (DSB)-induced byproducts and random biallelic targeting due to uncontrollable Cas9 targeting activity. Here, we establish a parental allele-specific gene-targeting (Past-CRISPR) method, based on the detailed observation that pronuclear transfer-mediated cytoplasmic dilution can effectively terminate Cas9 activity. We apply this method in embryos to efficiently target the given parental alleles of a gene of interest and observed little genomic mosaicism because of the spatiotemporal control of Cas9 activity. This method allows us to rapidly explore the function of individual parent-of-origin effects and to construct animal models with a single genomic change. More importantly, Past-CRISPR could also be used for therapeutic applications or disease model construction.